Consumers' behaviour towards modern and traditional retailing in Kuching city - Awang Yusop, Awang Adom (2014)
The retailing market in Kuching city has undergone dynamic changes. New modern retail chains' entering the Kuching retail industry is creating intense competition among all the large and small players active in the market. However, some portion shares of the market are still in the hands of small traditional retail owners. The main issue and problem of this study is the consumers' preference of shopping choice and satisfaction of retail formats and a question of continuous growth and sustainability of modern retailers despite of the continuous existence of traditional retailers. The purpose of this study is to identify the important factors that affect consumer shopping behaviour of Kuching city customers toward modern and traditional retailers. The study focuses to find factors that lead to the shopping choice and satisfaction and which specific type of retail formats are of better customers' preferences. Based on the literature review, a theoretical model was proposed and six hypotheses were developed. The model investigates the effect of several independent variables on store attributes: product, price, promotion, store atmosphere, location convenience and services. A survey of 209 respondents of Kuching city consumers are the sample representing Kuching city population customers responded to survey questionnaire based on a non-probability sampling approach of convenience sampling. Several techniques were used with the help of Statistical Package for Social Sciences (SPSS) to analyze the data, such as frequency, mean, Pearson's correlation, linear regression analysis and SEM equation analysis. The finding shows that products, prices, promotions, store atmosphere, locations, and services have significant impact on shopping choice of both modem and traditional retail formats. The most important variables are services and store atmosphere that influence Kuching city customers to shop at modern retailers. The prices and promotions are the most important variables that influence Kuching city customers to shop at traditional retailers. The three types of retail format: hypermarket, supermarket and traditional markets are relevant to Kuching city customers. The most preferred retail format of Kuching city customers is supermarket followed by traditional markets and hypermarket is least preferred.